2008
DOI: 10.1111/j.1752-7325.2007.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health of Young Children in Mississippi Delta Child Care Centers: A Second Look at Early Childhood Caries Risk Assessment

Abstract: Parental abscess and parent's report of the child's oral health-related OOL are risk indicators for poor oral health outcomes that could be used by nondental personnel to identify young children in need of early preventive intervention and dental referral

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
(23 reference statements)
2
9
0
5
Order By: Relevance
“…Not all beneficial practices, however, had beneficial effects on dental caries; in this study, the frequency of tooth-brushing and/or toothbrushing with supervision did not have a positive influence on the child's caries experience. Although this agrees with some studies 27,28 , others have reported lower caries levels associated with frequent tooth-brushing 20,29 . The controversial results and conclusions may be due to acidogenicity of biofilm or poor tooth-brushing techniques of children and/or their caregivers.…”
Section: Discussionsupporting
confidence: 93%
“…Not all beneficial practices, however, had beneficial effects on dental caries; in this study, the frequency of tooth-brushing and/or toothbrushing with supervision did not have a positive influence on the child's caries experience. Although this agrees with some studies 27,28 , others have reported lower caries levels associated with frequent tooth-brushing 20,29 . The controversial results and conclusions may be due to acidogenicity of biofilm or poor tooth-brushing techniques of children and/or their caregivers.…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that the family SES is closely related to the occurrence of caries 18 . In this study, we found that family income was not associated with the incidence of caries, whereas low education and less oral knowledge of parents, more number of children in the family, and rural residence were significantly related to the occurrence of caries, which is consistent with other studies 19,20 . In addition, we also found that the incidence of caries was significantly higher in private childcare providers than in public ones.…”
Section: Discussionsupporting
confidence: 92%
“…[32] Nonetheless, for many years, the application of questionnaire has demonstrated to successfully capture highly reliable information on respiratory disease. [22] 2) The diagnosis of dental caries was made visually without use of X-rays. 3) The prevalence of nocturnal asthmatic symptoms was lower than the overall prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…We chose these confounders because they demonstrated a strong association with dental caries in previous studies. [21][22][23] Sugar consumption antecedent was determined by questions on the questionnaire to which children's parents responded, on the type, quality and quantity of foods and beverages consumed by the children while they watched television, as well as the frequency with which children consumed snacks (defined as any food consumed between the main meals including breakfast, lunch and dinner). Questions documenting children's food-consumption habits and lifestyles were taken from the questionnaire applied at the Mexican National Health and Nutrition Survey 2006.…”
Section: Data From Questionnairementioning
confidence: 99%